Tingkat pengetahuan siswa tentang pembelajaran renang kelas VII di SMPN 1 Banyusari Kabupaten Karawang - Aprizal, Muhamad; Nasution, Nana Suryana; Sumarno, Ardawi; Fauzi, Dira (Universitas Hamzanwadi, 2024)
This study aims to assess the level of student knowledge about swimming lessons. The research method uses a survey method with a questionnaire. Based on the results of the study, the level of student knowledge about swimming lessons is in the